2014
DOI: 10.3892/br.2014.397
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Rheb(S16H) in substantia nigra pars compacta dopaminergic neurons in vivo

Abstract: Abstract. Although there are ongoing intensive research efforts, no effective pharmacological therapies for Parkinson's disease (PD) have been developed thus far. However, with the development of efficient gene delivery systems, gene therapy for PD has become a focus of research and increasing evidence suggests that continuous production of neurotrophic factors play a significant role in the functional restoration of the nigrostriatal dopaminergic (DA) system. Our recent study reported that the transduction of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…In particular, Rheb(S16H) upregulation by adeno-associated virus serotype 1 (AAV1) administration in nigral dopaminergic neurons significantly increased the activation of mTORC1, resulting in greater neuroprotective effects compared with Rheb(N153T) upregulation in the animal model of PD [24]. In addition, our studies demonstrated that the upregulation of neuronal Rheb(S16H) could protect neurons against neurodegeneration and promote axonal regrowth in the nigrostriatal dopamine system and hippocampus of the adult brain [11,24,25,30,69,134]. The activation of mTORC1 induced by Rheb(S16H) transduction of hippocampal neurons was found to result in BDNF production, which protected against thrombin-induced neurotoxicity in the rat hippocampus [5].…”
Section: Mutation Of Rheb Leading To Constitutive Activationmentioning
confidence: 78%
“…In particular, Rheb(S16H) upregulation by adeno-associated virus serotype 1 (AAV1) administration in nigral dopaminergic neurons significantly increased the activation of mTORC1, resulting in greater neuroprotective effects compared with Rheb(N153T) upregulation in the animal model of PD [24]. In addition, our studies demonstrated that the upregulation of neuronal Rheb(S16H) could protect neurons against neurodegeneration and promote axonal regrowth in the nigrostriatal dopamine system and hippocampus of the adult brain [11,24,25,30,69,134]. The activation of mTORC1 induced by Rheb(S16H) transduction of hippocampal neurons was found to result in BDNF production, which protected against thrombin-induced neurotoxicity in the rat hippocampus [5].…”
Section: Mutation Of Rheb Leading To Constitutive Activationmentioning
confidence: 78%
“…NSC self-renewal and differentiation are vital processes at various stages of brain development. Overactive mTORC1 encourages NSC differentiation at the expense of self-renewal in neonatal NSCs, while reduced mTORC1 activity prevents differentiation, resulting in fewer neurons [103]. Additionally, due to its involvement in Reelin-Dab signaling, constant activation of Rheb1 in NPCs influences neuroblast migration [104].…”
Section: Rheb1 In Neural Stem Cell Differentiationmentioning
confidence: 99%
“…Our previous studies also demonstrated that the substitution of serine by histidine at position 16 of Rheb [Rheb(S16H)] significantly induced the expression of NTFs, such as GDNF, CNTF, and BDNF in the adult brain [ 39 , 42 , 69 , 73 , 74 , 179 , 180 ]. Our studies further showed that the upregulation of neuronal Rheb(S16H) protects neurons from neuronal degeneration and promotes axonal regrowth in the hippocampus and the nigrostriatal dopamine system of the adult brain [ 41 , 73 , 74 , 149 , 150 , 180 ]. Our laboratory research further demonstrated that the activation of mTORC1 induced by Rheb(S16H) transduction in hippocampal neurons led to BDNF production, which protected the rat hippocampus against thrombin-induced neurotoxicity [ 40 ].…”
Section: Therapeutic Potential Of Rheb(s16h) Transduction Via Aav1mentioning
confidence: 99%